HUBUNGAN DUKUNGAN SOSIAL MERAWAT BAYI BARU LAHIR DENGAN KEJADIAN DEPRESI POSTPARTUM DI PRAKTIK MANDIRI BIDAN WULANDARI - Shelvi Ovi Lestari (Health Care Media, 2024)
Postpartum depression or postpartum depression is a condition that can occur in women in the postpartum period. No one expects that they will experience this, because in general women who are pregnant, especially those for the first time, are certainly looking forward to the arrival of their baby. The main factor that influences postpartum depression is the social support provided by the husband and family. Husband and family support, namely emotional relationships, communication and closeness and marital satisfaction. The risk of depression will increase if the mother who gives birth does not receive support from her husband and family. Based on the research, it was found that the value of p = 0.013 < α = 0.05, which means that H0 is rejected or there is a relationship between social support caring for newborns and the incidence of postpartum depression.